PENGETAHUAN, SIKAP, DAN PRAKTEK PEMBUDIDAYAAN IKAN KURAMBAH UNTUK MENINGKATKAN KESEJAHTERAAN KELUARGA DI SEKITAR DANAU BATUR - Simbung Arimbawa, Nengah; T. Suryadhi, Nyoman; Artini, Ni Wayan Putu; Santiyasa, Wayan (PIRAMIDA, 2012)
A study on knowledge, attitude, and practice of families living at the edge of Batur lake on fish cultivation for prosperity improvement was carried out in the community of banjar Dalem Songan village, Kintamani. Covering 40 households selected for this study, head of the households or member of the family actively participated in the fish cultivation was to be the respondents. Data were collected using questionnaire by house to house visit. Using indicators implemented by BKKBN for diagnosing poverty level of families found that families in this study are still in the condition of highly poverty level mainly associated with a high percentage of families using soil for floor. Meanwhile, knowledge and attitude of families surrounding are strongly supported establishment or development of fish cultivation regardless of low earning received from harvesting and selling the fish. Difficulty in getting capital for both starting and developing fish cultivation, high percentage of fish mortality, and marketing problems for the harvested fish are amongst problems experienced by those families already actively handling fish cultivation. Therefore it is recommended that families living at the edge of Batur lake actively seek opportunities for prosperity improvement through improving knowledge and skill on marketing, capital earning, and reducing fish mortality in fish cultivation activities. In addition, institutions such as banking, fishery, service department, university, and private or community organization can actively take part to achieve the objective of family prosperity improvement through fish cultivation activities.
Keywords: fish cultivation, poverty level, prosperity improvement